Implikasi Putusan Mahkamah Konstitusi Nomor 35/PUU-X/2012 terhadap Pengaturan Hutan Adat dan Dampaknya terhadap Hak Masyarakat Adat - Paulus Pora Putra Fajar; Sukardan Aloysius; Husni Kusuma Dinata (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
The Constitutional Court's decision confirms that customary forests are no longer state forests. This decision concerns two issues, namely, regarding customary forests and conditional recognition of the existence of indigenous communities. Legal issues, what are the implications of the Constitutional Court's decision on the regulation of customary forests and its impact on the rights of customary law communities. Aims to determine the implications of the Constitutional Court's decision on customary forest regulation and its impact on the rights of customary law communities. Types of normative research. Library study data collection techniques. The types of approaches are the statutory approach, contextual approach, historical approach, comparative approach and analytical approach. Using primary and secondary legal materials. Qualitative descriptive analysis. The research results show that Constitutional Court Decision has implications for forestry regulation in the form of creating implementing regulations governing customary forests that have developed significantly. The impact of the decision on customary law communities is, namely, the positive impact, customary law communities are recognized as owners of customary forests and the negative impact, the conditionality of recognition of the existence of customary law communities is increasingly strengthened.